Compound heterozygous FAM20C gene variants in a patient with severe Raine syndrome: a case report - Chirteș, Camelia; Bogliș, Alina; Toth, Andrea; Rac, Corina; Bănescu, Claudia (Frontiers in Genetics, 2023)
Raine syndrome is a congenital disorder caused by biallelic mutations in the FAM20C gene. While most diagnosed cases of the syndrome are lethal in the first few months of life, there are also reports of non-lethal cases with Raine syndrome. The characteristic of this syndrome is typical facial dysmorphism and generalized osteosclerosis, as well as possible intracranial calcification, hearing loss, and seizures. We report a case of a 4-day-old patient at the time of examination, born with a distinct facial dysmorphism, short neck, narrow chest, and curved tibia. The parents, affirmative gypsy and non-consanguineous, had a previous male child born with the same phenotype who died at four months old. The computed tomography scan revealed choanal atresia, while transfontanelar ultrasound showed hypoplasia of the frontal and temporal lobes, corpus callosum dysgenesis, and multiple areas of intracranial hyperechogenicity. The chest X-Ray revealed generalized increased bone density. A skeletal disorders gene panel was performed which identified two variants in the FAM20C gene: a pathogenic variant c.1291C>T (p.Gln431*) and a likely pathogenic variant (c.1135G>A) (p.Gly379Arg), confirming the clinical diagnosis. The parents were also tested, and each was found to carry one of the variants. The particularity of this case is the severe phenotype in a compound heterozygous case that consists of FAM20C c.1291C>T (p.Gln431*) variant that has recently been reported in the literature. Also, our case is one of the few compound-heterozygous mutations in the FAM20C gene that has been described in a non-consanguineous marriage.